AGRONOMIC EFFICIENCY OF FERTILIZERS BASED ON HUMUS, ROCK POWDER, AND MINERALS ON SOYBEAN YIELD IN PARAGUAY-PY - Marques, Mônica Lau da Silva; Jesus, Jéssica Maria Israel de; Santos, Wanderson Moreira dos; Silva, Jeferson Wendling Graciano; Martins, Adriana Lau da Silva; Marques, Valter Santos (REVISTA DE AGRICULTURA NEOTROPICAL, 2020)
Soybean is the most commercially cultivated crop in Paraguay, and obtaining high yields requires the application of large amounts of fertilizers, raising the cost of production. Developing strategies for the efficient use of applied nutrients is necessary. Therefore, the study aimed to evaluate the agronomic efficiency of combinations of mineral fertilizers with organic matter and rock powder in the development, nutrition, and yield of soybean. The experiment was carried out in Hernandarias, Paraguay, in the 2016-2017 harvest. The different fertilizers influenced the absorption of Zn, Mg and K, and grain yield. Among the treatments, the highlight was the agronomic efficiency index obtained by the replacement of 30% of mineral fertilizer by humus, presenting grain yield of 3219, 67 kg ha-1. However, it was equal to the mixing 30% of humus + rock powder with 70% of NPK formulation 04:40:10 with grain yield of 3206.50 kg ha-1, and the mixing 20% of humus + rock powder with 80% of NPK formulation 04:40:10 with grain yield of 3165.17 kg ha-1. Thus, it is recommended to use rock powder and humus in soybean production in Paraguay, especially in Latossolos (Oxisols) that have little organic matter and low CTC.